Characterization Of Modern Water Isotopes Of Northeast Monsoon Precipitation In Kelantan - Jamian, Nurul Sufiana (2019)
The characteristics of oxygen-18 and deuterium in precipitation were investigated to understand the input mechanism of the water cycle during NEM season from the year 2013 to 2016. The isotopic composition of Kelantan precipitation reflects the monsoon signature across time. It demonstrates a little variation of isotopic values for δ18O and δ2H in Peninsular Malaysia precipitation which reflects the regional climatic setting that driven by ITCZ. Despite consistent climate system, the precipitation may have potential natural hazard to Kelantan watershed in 2014. Continuous moisture supply is observed showing the enrichment in the isotopic composition during that particular year. Furthermore, it has been observed that the isotopic variation of 2015 precipitation was characterized by the El Nino phenomenon. Highest D-excess reading (14.48%₀) was recorded in December 2015 suggesting dry condition effect from this event. While for 2013 and 2016, the results demonstrate common isotopic characteristic which follows the Rayleigh distillation concept.